Taman Indoor Bonsai Pekanbaru Dengan Pendekatan Arsitektur Organik - Sabila Khalmi; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indoor Park allows users to enjoy the beauty of nature comfortably. Bonsai as an art of miniaturized plants which always popular can filled the indoor park to become a natural tourist attraction, education for the community and commercial for gardening and bonsais in the city of Pekanbaru. Based on data collection, literature study, comparative study, and empirical study, the concept of